State-Owned Enterprise’s Debt in the State Financial Regime - Hidayatulloh Hidayatulloh; Éva Erdős (Sriwijaya Law Review, 2023)
Several Indonesian State-Owned Enterprises (SOEs) have had very high debts recently. Several reasons, such as government assignment projects, the impact of the Covid-19 pandemic, and corrupt management behaviour, have caused the increase in liability. There is a fierce debate among academics and legal scholars regarding whether the SOE’s debt is state debt. A state company is an independent legal entity separate from the state and obtains capital from separated state assets. Besides, the state, as the majority shareholder, assigns SOEs to projects that support government programs even though they are not profitable. In addition, several SOEs often receive State Equity Participation to survive bankruptcy caused by running out of capital or large debts. This paper will analyse the country's debt status from the perspective of public finance by taking the case of Indonesia. Moreover, it will explore the theoretical and empirical aspects of SOE’s debt from a state finance point of view. This study will use doctrinal legal research to interrogate the law as it is and should be. Although this research concludes that SOEs' finances are a state financial regime, the supervision of SOEs is not Government Judgment Rules but Business Judgment Rules. SOE's debt is the responsibility of SOE as a corporate legal entity. In the case of Indonesia, the government often rescues SOEs that have failed to pay their debts through State Equity Participation and/or privatisation while maintaining most state ownership shares, for instance, Garuda Indonesia, a national airline. Finally, state accountability for SOE's debt only occurs indirectly because of the financial separation between the state and companies. The Indonesian government saved Garuda Indonesia's finances to protect national assets and continue to control vital businesses. However, the state must also reform the management of SOEs so as not to harm state finances by upholding good corporate governance and preventing fraud and corruption.